A musicalização como dispositivo de intervenção precoce junto a bebês com risco psíquico e seus familiares - Ambrós, Tatiane Medianeira Baccin (2016)
This work carried out the study of the effects of the babies musical education, from the proposal of Esther Beyer, in reversing the psychological risk in a case of an infant with five months, which results in PREAUT signs suggesting future autistic structure. The music education took place with the participation of two other babies with seven months, mothers of three babies and, in some meetings, the brothers. In a total of ten meetings, the baby at risk participated in eight meetings. The effects were positive for the advancement of the baby towards psychic integration. There was also psychomotor, cognitive and linguistic progress. The other two babies have evolved in their musical behavior and socialization. Mothers also evolved in their behavior and bond with their children. Research has shown that musical education can be an effective early intervention mechanism in the case of psychological risk. Can be used exclusively or associated with individual clinical intervention. When considering the possible effects on family behavior and perception of family members who participated in the experiment, it can be concluded that music was a form of positive and effective early intervention, with the advantage of not presenting itself as a traditional therapy, which, often, it does not present the accession of the family.